(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the extent of organizational culture and the extent of school custom practices of public elementary school teachers. This study employed non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. One hundred twenty (120) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the extent of organizational culture was extensive while the extent of school custom practices of public elementary school teachers was also extensive. Moreover, the overall results disclosed that indicators for the organizational culture have a strong positive correlation to the school custom practices of public elementary school teachers. Further, results from the regression analysis revealed the following have a strong influence of organizational culture on school custom practices of public elementary school teachers: Leadership, Teamwork, and Adaptability. It was suggested that a sustainable organizational culture and application of its practices, implementing the three aspects of organizational culture. It was highly recommended to promote better school performance. It was also recommended secure and sustain better school leadership, management, and governance, participation of teachers is anticipated.